Sydenham's chorea: Long-term immunosuppression for psychiatric symptoms - Ben-Pazi, Hilla; Kroyzer, Naama; Hashkes, Philip J. (Journal of Pediatric Neurology, 2012)
Sydenham's chorea (SC) is, thought to be an autoimmune neuropsychiatric disorder that may have a prolonged fluctuating course. In some children, associated psychiatric symptoms such as depression, anxiety and obsessive-compulsive symptoms are unresponsive to neuroleptic therapy and may cause significant disability. We describe two adolescents with no prior neuropsychiatric disorders who developed SC and psychiatric symptomatology that did not respond to conventional psychiatric drugs: a 13-year-old boy with hallucinations and a 14-year-old girl with abulia. They received immunosuppressive therapy for 1 year. Hallucinations in the boy resolved following the yearlong regimen of corticosteroids and did not recur during the 5-year follow-up period. The abulia resolved after 14 weeks of prednisone treatment but recurred several months later; further treatment with prednisone and azathioprine resulted in complete resolution of the abulia over the next year. This report of immunosuppressive-responsive psychiatric symptoms in SC suggests an underlying autoimmune disorder causing behavioral changes and offers a therapeutic option in neuroleptic resistant cases.
Keywords: Depression; anxiety; obsessive-compulsive; prednisone; azathioprine